A 4-Day Mindfulness-Based Cognitive Behavioral Intervention Program for CFS/ME. An Open Study, With 1-Year Follow-Up - Stubhaug, Bjarte; Lier, Haldis O.; Aßmus, Jörg; Rongve, Arvid; Kvale, Gerd (Frontiers in Psychiatry, 2018)
Background: Chronic Fatigue Syndrome/ Myalgic Encephalopathy (CFS/ME) is an incapacitating illness for which no single treatment has been proven universally effective. The aims of this study were to: (1) explore the clinical course for patients with CFS/ME following a four day concentrated treatment program, (2) evaluate the clinical short and long term changes from pre- to post-intervention and (3) evaluate the satisfaction with the program. Methods: 305 patients, all fulfilling the Oxford criteria for CFS/ME, referred to a specialist outpatient clinic in a concentrated group intervention program, participated in an open uncontrolled study comprised by education, mindfulness sessions, cognitive group therapy sessions, physical activity and writing sessions, within a context of a mindfulness-based cognitive behavioural treatment model. Assessments were done by self-reports prior to the first consultation, one week before and one week after the intervention programme, and at 3 months and one year after the intervention. SPSS 23 and R 3.3 were used for statistical analyses. The associations between case definitions and the outcome measures (fatigue, SF-36 physical scale) were assessed by a linear mixed effects model (LME). Results: None of the patients dropped out of the program, and overall expressed high satisfaction with the content, focus and amount of treatment. Results showed significant clinical changes for 80% after the intervention, changes being sustained through one year after the program. Using the criteria from the PACE study concerning inclusion (Fatigue Scale >6/11, SF-36 Physical Function <65/100) and improvement, changes were statistically significant (p<.001). For both Fatigue Scale (FS) and the SF-36 there were significant effects of time from baseline to all time points with a significant drop in scores, applying the linear mixed effects model. Conclusion: Clinical changes observed from pre-treatment to one year follow-up could represent effects of the 4-days concentrated intervention program, and should be further explored in a controlled study.